A influência das capacidades dinâmicas no processo de contínuo ajustamento estratégico - Herrmann, Júlia Colombo Doebber (2013)
Recent research points to the need for further study on small businesses and on their internal capacity for adaptation in the context of continuous change. Miles and Snow (1978) suggest the existence of a continuous process of strategic adjustment and claim that organizations can discover and maintain the strategic fit between the organization and its environment, and internal fit among strategy, structure and management processes. Teece, Pisano and Shuen (1997) address the company's ability to "create, adapt and reconfigure" the internal and external routines. This study aims to validate the assumption that the process of continuous adjustment of enterprises is influenced by dynamic capabilities. A qualitative study involving a case study of a small business in the industrial area was proposed to characterize the internal fit among strategy, structure and process, which show the solutions to the problems facing the company entrepreneurial, engineering and management. Furthermore, longitudinal analysis of variables that characterize the company allowed the investigation of the motion to amend the strategic fit, the identification of organizational skills and the influence of dynamic capabilities in the process of continuous strategic adjustment mapped to this company. The analysis of the variables involved in this process reveals that: a) the strategic fit of the company is not stable, at first he is characterized as Prospector, and along the historical trajectory, it tends to be changed to the typology Analyzer; b) organizational skills tend to stabilize the strategic fit during the process of continuous adjustment c) the activities of adjustment and the life cycle of dynamic capabilities drive the changes throughout the process of continuous strategic adjustment. Understanding the strategic context of internal capacity to adapt the company provides grants to equip executives of small businesses in making decisions that could change the strategic course of business and to promote improved management.